Academic libraries in Leyte a survey with implications for library cooperation - Yap, Lilybelle D.; Buenrostro, Juan Jr. C.; Arlante, Salvacion M. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1990)
This descriptive research is a survey of the resources and facilities of the academic libraries in Leyte for the possibility of establishing library cooperation among them. Specifically, the study aims to 1) describe existing resources and facilities of academic libraries in Leyte; 2) determine the extent of library cooperation among academic institutions in Leyte; 3) find out the attitudes of the librarians in this area regarding library cooperation and resource sharing; 4) recommend possible areas where library cooperation and resource sharing can be undertaken among libraries in Leyte.
This survey is limited to the eleven libraries attached to private and state academic institutions in Leyte. These are Divine Word University of Tacloban (DWUT), Holy Infant College (HIC), Leyte Colleges (LC), Leyte State College (LSC), U.P. College Tacloban (UPCT), Saint Peter's College of Ormoc (SPCO), Western Leyte College (WLC), Franciscan College of the Immaculate Conception (FCIC), Northern Leyte College (NLC), the College of Maasin (CM), and Saint Joseph College (SJC).The main tool used for data collection was the survey questionnaire consisting of four sections: Section I calls for institutional data, Section II elicits information regarding library resources and facilities, Section III looks into library services, and Section IV deals with the attitudes of the librarians toward library cooperation.
Cooperation in the use of library facilities and interlibrary loan have been possible through informal and mutual agreement among the academic librarians. Willingness to join library cooperation among academic libraries in Leyte was expressed by all respondents but cited various reasons which hinder their participation. The main reason why majority of the librarians hesitate to join library cooperation activities is because the size of their library collection is rather small. They think that this is the principal deterrent factor in joining any library cooperative endeavor, when in fact, inadequacy of library collections can be overcome by sharing resources among the academic libraries. The second main reason cited is administrative constraints, which could mean the need for additional qualified library staff to do the job, library tools, equipment, and funds to support the library cooperation activities. Other reasons cited are: no one has initiated the library cooperation program; librarians are too busy with other activities; distance from one library to another library; insufficient staff training; inadequate tools; unawareness of the librarians of the value of library cooperation; and the thought that no benefit can be derived from cooperative activities.
By proximity, library cooperation among the academic libraries in Leyte, particularly among the libraries in Tacloban City, Ormoc City, and in Maasin in Southern Leyte is possible. In terms of location, NLC and FCIC may cooperate with the libraries in Ormoc City.
The study recommends that library cooperation among academic libraries must be initiated by the Leyte Librarians Association (LELA). The Association together with the academic librarians should seek the support of their administrators in planning and implementing library cooperation programs and activities, and conducting conferences to discuss the advantages of library cooperation and resolve the problems and issues which they are bound to encounter formal written agreements could be drawn up at the town, city, sub-provincial level, or among all the academic libraries in Leyte in the following cooperative activities in which the libraries signified willingness to join: staff training and development, interlibrary loan, servicing clientele of other libraries, preparation of union catalog, shared use of selection tools, centralized solicitation of gifts and exchange, cooperative cataloging, indexing of periodicals, and cooperative acquisition of books. The other activities which are not highly considered by the respondents at present can be developed and undertaken later.
Typescript.
Special Problem (Master of Library Science)
Keywords: Libraries, University and colleges -- Philippines -- Leyte; Library cooperation -- Philippines -- Leyte